Machine learning, optimization, and big data : Second International Workshop, MOD 2016, Volterra, Italy, August 26-29, 2016, Revised Selected Papers /: Second International Workshop, MOD 2016, Volterra, Italy, August 26-29, 2016, Revised Selected Papers. (2017) - Unknown
No abstract available